2023
DOI: 10.1186/s12879-023-08414-6
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus dissemination with necrotizing hepatitis following Descemet membrane endothelial keratoplasty

Abstract: Background Corneal transplants are the most common type of transplant and increasing in frequency. Donor cornea tissues are a rare source of herpes simplex virus (HSV) transmission and not routinely tested for presence of HSV. Donor graft-to-recipient transmission typically causes graft failure and anterior uveitis, and extra-ocular HSV disease has not been previously reported. We present a case of HSV transmission from donor cornea tissue that nearly cost the corneal transplant recipient his l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Tear fluid exosomes may be a site of HSV-1 Latency; involved in the spread of HSV-1 infection to human corneal epithelial cells (HCECs). Corneal grafts can also be a source of HSK infection if not properly screened[ 224 ]. With a global shortage of available viable cornea graft tissue, Li et al [ 225 ] demonstrated that porcine corneal tissue is a good option for human corneal tissue[ 225 ], Recurrent HSK has been implicated in Deep Anterior Lamellar Keratoplasty failure[ 226 ].…”
Section: Recurrent Herpes Simplex Keratitis: Clinical Features and Pr...mentioning
confidence: 99%
“…Tear fluid exosomes may be a site of HSV-1 Latency; involved in the spread of HSV-1 infection to human corneal epithelial cells (HCECs). Corneal grafts can also be a source of HSK infection if not properly screened[ 224 ]. With a global shortage of available viable cornea graft tissue, Li et al [ 225 ] demonstrated that porcine corneal tissue is a good option for human corneal tissue[ 225 ], Recurrent HSK has been implicated in Deep Anterior Lamellar Keratoplasty failure[ 226 ].…”
Section: Recurrent Herpes Simplex Keratitis: Clinical Features and Pr...mentioning
confidence: 99%
“…A relevant feature of these pathogens is the establishment a lifelong latent infection in neuronal cells that innervate the infected epithelium and periodical reactivation following various environmental cues. Genital herpes can cause severe or fatal infection in newborns through vertical congenital transmission from the mother to the infant [5,6] and can lead to severe complications in immunocompromised patients [7][8][9]. Of note, HSV-2 is strongly correlated to HIV infections [10,11].…”
Section: Introductionmentioning
confidence: 99%